(untitled) (Scientific journal of the Fergana State University, 2024)
The most important task of phraseology is to differentiate and distinguish phraseological units from phrases formed in speech (i.e., not ready in advance), and on this basis to determine the characteristics of phraseological units. Depending on the specific differences between idioms and phraseological units, phraseological combinations and set sentences(proverbs and proverbs, other phraseological units equivalent to sentences), many researchers understand phraseology in two directions: narrow and broad. In a broad sense, the framework of phraseology also includes proverbs and sayings, set sentences characteristic of folklore, and some forms of communication (greetings, farewell sentences). But this question, that is, the question of understanding phraseology in a broad sense, still remains controversial. The main tasks or issues of phraseology: determine the consistency of phraseological content and, in connection with this, study the sign(s) of phraseology; description of homonymy, synonymy, antonymy, polysemy and variations of phraseology; identify the specific features of words used in phraseology and their specific meanings; clarification of the relationship between phraseology and groups of words; clarify their syntactic role; studying the formation of new meanings of words as part of phraseological units, etc. Phraseology develops principles for dividing phraseological units, methods for their study, classification and description in dictionaries. Based on specific, diverse methods developed in phraseology, the phraseological structure of a language is classified according to various: structural-semantic, grammatical, functional and methodological grounds.